Improvement of intermediate vision with new monofocal intraocular lenses: A systematic review and meta-analysis. Issue 3 (May 2023) - Redruello-Guerrero, Pablo; Rivera-Izquierdo, Mario; Jiménez-Gutiérrez, Carmen; Láinez-Ramos-Bossini, Antonio Jesús; Yela, Rubén; López-Marín, Ignacio
Purpose: Monofocal intraocular lenses (IOLs) used in cataract surgery are designed to improve visual acuity (VA). The available evidence of new monofocal IOLs" functional benefits is limited. The aim of this meta-analysis was to analyze the improvement in VA using Tecnis Eyhance monofocal IOLs compared to standard monofocal IOLs Tecnis ZCB00. Methods: MEDLINE, Web of Science and Scopus were searched for studies assessing improvement in intermediate VA using Tecnis Eyhance IOLs versus Tecnis ZCB00 IOLs. Studies evaluating post-operative VA in patients who underwent cataract surgery were selected. This meta-analysis followed PRISMA guidelines and was registered in PROSPERO. The Cochrane Risk of Bias Tool 2.0. was used to assess the methodological quality of the included studies, risk of selection bias and comparability of cohorts and outcomes. Results: The search resulted in 1153 articles. Five studies met the inclusion criteria and were included in the meta-analysis. A total of 604 eyes were evaluated, of which 309 received Tecnis Eyhance IOLs and 295 were implanted with Tecnis ZCB00 IOLs. Mean binocular distant-corrected intermediate VA with Tecnis Eyhance IOLs at 2 weeks-1 month showed a significant difference of −0, 21 logMAR, p < 0.001; and mean binocular distance-corrected intermediate VA with Tecnis Eyhance IOLs at 6 months showed a significant difference of −0, 11 logMAR, p < 0.001. Conclusion: Near VA could not be assessed in this meta-analysis as it was measured in very few studies. Preliminary pooled evidence indicates that intermediate VA improved with Tecnis Eyhance IOLs. Further studies evaluating near VA and with longer follow-up are still necessary.